Activation of the c-Jun transcription factor following neurodegeneration in vivo - Schenkel, Johannes (Neuroscience letters, 2004)
Neurodegenerative diseases often result in neuronal cell death, but the molecular mechanisms responsible are not fully understood. The expression and activation by phosphorylation of the c-Jun transcription factor plays an important role for the fate of affected neurons in response to injury. c-Jun is phosphorylated at serines 63 and 73 by the c-Jun N-terminal kinases and c-Jun N-terminal phosphorylation augments the transcriptional activity of c-Jun. Two approaches in neurodegeneration were investigated: The transection of the medial forebrain bundle to study neuronal cell body response in the derived neuronal populations of the substantia nigra pars compacta (SNC). This model of central axotomy leads as a long-term reaction to degeneration of the affected SNC neurons. A central component of the axotomy-induced alterations leading to neuronal degeneration is the rapid induction, lasting expression and activation of the c-Jun transcription factor. The focal cerebral ischemia, induced by occlusion of the arteria cerebri media and the subsequent reperfusion, serves as a suitable in vivo model for stroke. Also, ischemia leads to upregulation and activation of c-Jun and its target genes. Here the key role of c-Jun for the fate of neurons following degeneration is discussed with data received from experiments performed in Manfred Zimmermann's department investigating the effects of c-Jun on its target genes and on factors influencing c-Jun expression and activation.